Patterns of mature woody plant species encroachment on vegetation structure, density, and diversity of the understory layer across the Marikana Thornveld - Mangwane, Mziwanda; Madakadze, Ignacio Casper; Tjelele, Tlou Julius; Ramoelo, Abel (Frontiers in Ecology and Evolution, 2025)
IntroductionBush encroachment has a negative impact on the vegetation structure, ecosystem functions, and services of savanna rangelands. Woody plant encroachment creates an imbalance in the grass-to-tree ratio, leading to a decline in ecosystem services, including grazing capacity and soil nutrients.MethodsThis study aimed to evaluate the vegetation structure, diversity, and relationships of tree species across four different growth stages in the Marikana Thornveld. Three sites were identified at the Roodelpaat experimental farm, where six 1-hectare plots were established. In each plot, nine 10 m × 10 m subplots were set up to identify mature woody plants, shrubs, and saplings. Seedlings were identified within three 1.69 m² quadrats nested within each subplot.Results and discussionThe study identified a total of 9,028 individual woody plants, including 158 seedling species, 161 saplings, 159 shrubs, and 154 mature woody plant species. The regression line plotted seedling density against the densities of mature trees, shrubs, and saplings, with b values significantly less than 1, indicating a negative impact of mature trees, shrubs, and saplings on the seedling layer. Seedling abundance displayed a non-linear relationship with mature trees, indicating a 4.75% representation of seedling abundance within the mature tree layer. Woody seedling species exhibited the highest abundance across four growth stages. Overall, across all woody plant species at different growth stages, there was a general decline in the woody density class, resulting in a J-shaped curve pattern. Seedlings and mature trees exhibited the highest diameter at breast height (dbh) proportions among individual woody plants from the first to the third DBH size classes, followed by a decline.ConclusionGenerally, these results highlight a weak relationship between mature woody plant species and the understory layer, including shrubs, saplings, and seedlings. Consequently, mature woody plants cannot predict the establishment of understory woody plants or the recruitment of seedlings as a cause of bush encroachment.